Expression of Androgen Receptor in Breast Carcinoma and Its Correlation with Estrogen, Progesterone, and Human Epidermal Growth Factor Receptor-2 Status - Nangru, Mayank; Agarwal, Ruchi; Singh, Kulwant; Garg, Mohinder Kumar; Kaur, Swaran; Hooda, Sunaina (Annals of Pathology and Laboratory Medicine, 2024)
Background: Breast cancer is the second most common cancer overall and the most common cancer in women. Immunohistochemistry has become a prerequisite in diagnosing, deciding therapy, and predicting prognosis for carcinoma breast. Despite this, it is still difficult to find targeted therapies for triple-negative breast cancer. Many therapies based on the use of androgen receptor agonists or antagonists are emerging. This study was intended to find the prognostic and therapeutic use of androgen receptors in breast carcinoma cases. Methods: This study was conducted in the Department of Pathology at Bhagat Phool Singh Government Medical College for Women, Khanpur Kalan, Sonepat, with 45 histologically confirmed breast cancer cases with known status of ER, PR, and HER-2/neu receptors. Results: The age of the patients ranged from 21 to 70 years, and the mean age was 48.24 years. Overall positivity for AR was observed in 62.22% of cases. An inverse relationship was observed between AR positivity and histologic grade. AR positivity was higher in cases that were ER-positive (72.72%), PR-positive (76.92%), and HER-2/neu positive (73.33%) in contrast to cases that were ER-negative (58.82%), PR-negative (56.25%), and HER-2/neu negative (56.67%). Conclusions: The authors concluded that AR is a more frequently expressed marker than other biomarkers in breast carcinoma cases. AR is associated with lower histologic grade and a good prognostic group of NPI. AR is expressed in high percentages in ER, PR, and HER-2/neu positive cases.